2022
DOI: 10.1590/0102-311xen231921
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the appropriate management of syphilis patients in primary health care in different regions of Brazil from 2012 to 2018

Abstract: This study aimed to analyze the presence of adequate infrastructure and work process in primary health care for the diagnosis, management, and treatment of syphilis in Brazil in 2012, 2014, and 2018. This is a cross-sectional, nationwide study with data from the three cycles of the Program for Improvement of Access and Quality of Basic Healthcare (PMAQ-AB): 2012 (Cycle I), 2014 (Cycle II), and 2018 (Cycle III). Two outcomes were assessed: adequate infrastructure and work process. The independent variables were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
8
0
4
Order By: Relevance
“…A acessibilidade deve ser levada em consideração quando da implantação de políticas públicas, em especial, para as populações mais vulneráveis, que historicamente já demostram dificuldades em acessar os serviços de saúde. 16 Há três níveis de barreiras de acesso: individual, comunitário e do próprio sistema de saúde. 17 O primeiro está relacionado às questões de estigma internalizado nos pacientes, percepção de ser visto como anormal e baixa autoestima, características principalmente encontra-das entre as mulheres trans, baixo nível socioeconômico, que os levam a falta de recursos para transporte e despesas médicas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A acessibilidade deve ser levada em consideração quando da implantação de políticas públicas, em especial, para as populações mais vulneráveis, que historicamente já demostram dificuldades em acessar os serviços de saúde. 16 Há três níveis de barreiras de acesso: individual, comunitário e do próprio sistema de saúde. 17 O primeiro está relacionado às questões de estigma internalizado nos pacientes, percepção de ser visto como anormal e baixa autoestima, características principalmente encontra-das entre as mulheres trans, baixo nível socioeconômico, que os levam a falta de recursos para transporte e despesas médicas.…”
Section: Discussionunclassified
“…Há persistência histórica de desigualdades na distribuição da infraestrutura adequada de UBS no Brasil, ressaltando a maior fragilidade no atendimento aos mais pobres e vulneráveis. 16 O fortalecimento da atenção básica é o caminho para a melhora da qualidade dos serviços, promovendo a melhoria da acessibilidade, pois é um espaço onde se consegue abordar as questões de confidencialidade, privacidade e de estigma. O estigma e a rejeição da sociedade frequentemente resultam em comportamentos de recusa em procurar serviço de saúde, atrasando o diagnóstico, interferindo na notificação efetiva do parceiro e, consequentemente, impedindo o controle das epidemias de IST.…”
Section: Discussionunclassified
“…These data are in agreement with the sociodemographic characteristics described in other studies [ 13 , 27 29 ]. However, the expansion of primary health care in Brazil led to an increase in prenatal coverage and the coverage of prenatal screening exams, a measure that expanded access and service as well as improved the diagnosis and notification of syphilis cases in the country [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The notification on the staging of the clinical phases of syphilis showed that more than 30% were reported as primary syphilis, 9% as tertiary syphilis and 21% as not informed. Since most cases in pregnant women are asymptomatic, diagnosed by serological tests in the latent form of infection [ 33 ], these data may be classification errors and provide evidence of the need to continuously train health care providers to improve the possibility of adequate treatment and the quality of surveillance data in the border region [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Syphilis is a sexually transmitted infection (STI) that is systemic and caused by Treponema pallidum. It constitutes to present a serious public health problem in Brazil and the world [ 1 , 2 , 3 , 4 ], despite the existence of methods of prevention, diagnosis, and treatment with an antibiotic, which is widely used as the gold standard for treating syphilis [ 5 , 6 , 7 , 8 , 9 ]. Moreover, it presents substantial morbidity, mortality, and chronic evolution and is a gateway to other STIs [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%